Studying management critically - Alvesson, Mats, 1956-; Willmott, Hugh (Sage Publications, 2003)
Drawing upon a range of influential contemporary movements in the social sciences, this text provides a wide-ranging analysis of management and its various specialisms. The book offers critical understandings of key areas of management theory and practice such as: accounting; strategic management; marketing; business ethics; and environmental management.